An outbreak of Legionnaires' disease in newborns in Serbia. (3rd April 2022) - Djordjevic, Zorana; Folic, Marko; Petrovic, Ivana; Zornic, Sanja; Stojkovic, Andjelka; Miljanovic, Ana; Randjelovic, Sladjana; Jovanovic, Snezana; Jovanovic, Milica; Jankovic, Slobodan
ABSTRACT: Legionnaires' disease is an atypical pneumonia caused by inhaling small droplets of water containing the bacterium Legionella spp. In newborns, it is a rare event, usually associated with water births and the use of air conditioning systems or air humidifiers. A nosocomial outbreak of Legionnaires' disease in the maternity ward of a secondary-care hospital in Arandjelovac, Serbia is described. Two male newborns were found to be infected with Legionnella pneumophila . On Days 7 and 6 of life, respectively, they were transferred to a tertiary-care hospital with signs of severe pneumonia which was radiologically confirmed. L. pneumophila was detected in tracheal secretions from both infants by RT-PCR, and its antigens were also positive in urine samples. The source of infection in the secondary-care hospital was the internal hot water heating system, and the main contributory factor to the emergence of the infection was the low temperature of the hot water which did not kill the bacteria during the available exposure time. These two cases highlight the importance of being cautious about possible Legionnaires' disease in maternity wards with outdated or irregularly maintained internal water supply systems. The adoption of official guidelines for the control and regular maintenance of water supply systems, including the multidisciplinary cooperation of all relevant parties, forms the basis for direct monitoring for Legionella and the prevention of new outbreaks. Abbreviations: BCYE: buffered charcoal yeast extract agar; GVPC: glycine vancomycin polymyxin cycloheximide agar; LD - Legionnaires' disease; TR-PCR: Reverse transcription polymerase chain reaction